An efficient synthesis of 9‐anthrone lactone derivatives via the Knoevenagel condensation and intramolecular cyclization. (7th February 2020) - Tan, Weiqiang; Zheng, Jifang; Guan, Jing; Zhan, Xiuzhi; Gao, Liming; Lyu, Lili; Shan, Bin; Yang, Qipeng; Ma, Mingliang; Xia, Yan
Abstract: One‐step synthesis of 9‐anthrone lactone derivatives from 1‐acetyloxyanthraquinone with a variety of dicarbonyl substrates in the presence of K2 CO3 by Knovenagel condensation and intramolecular cyclization is developed. Possible reaction mechanisms have been investigated using the density functional theory (DFT), which has been widely used in the study of reaction mechanism. The strategy could be useful for the synthesis of the core structure of marine natural product aspergiolide. Abstract :